(untitled) (Tanzania Medical Journal, 2017)
Introduction: Prostatic diseases are a very common in men over 40 years of age and pose a significant risk in terms of morbidity and mortality. Globally, benign prostatic hyperplasia (BPH), prostatic cancer and prostatitis are the most common conditions mainly presenting with lower urinary symptoms or symptoms related to complications of urinary bladder obstruction. Despite the relatively high prevalence of prostatic diseases, there is paucity of literature on in most developing countries, East Africa inclusive. The aim of this study was therefore to conduct a retrospective review of all prostatic biopsies submitted to private histopathology laboratory in Central, Tanzania in order to understand the clinical and histological pattern of the diseases.Methodology: This was a retrospective laboratory-based descriptive study. The study involved review of the available prostatic biopsy database for a period of one year, from February 2014 to February 2015.Results: Benign prostatic hyperplasia (61.6%) and prostate cancer (28.3%) are the most prevalent clinical diagnoses. They often presented with lower urinary tract symptoms (45.5%) and urinary retention (41.5%), although a significant proportion of cases were missing clinical information (10.1%). Histologically, BPH was the most common prostatic disease (60%), followed by prostate cancer (24.1%) and prostatitis (15.9%). The likelihood of making correct clinical diagnosis of BPH and cancer of prostate was consistently low (66.3% and 51.9% respectively). Despite clinical suspicion of prostatic cancer, there was high preponderance by clinicians to perform prostatectomy (80%), contrary to standard recommendation. Most histologically confirmed prostatic cancer had unfavorable scores in terms of histological extent of tumor (63.6%) and Gleason’s sum (92.9%).Conclusion: This study has demonstrated that clinical and histological patterns of prostatic diseases are similar to other studies, most of which are presenting with lower urinary tract symptoms and urinary retention. The accuracy of clinical diagnosis is low and a significant number of clinically suspected cases of prostate cancer underwent surgical operation, many of whom had unfavorable prognostic scores.Recommendations: It is recommended that clinicians should: scale up clinical vigilance and index of suspicion in dealing with cases of prostatic diseases, provide necessary information to histopathologists, and adhere to guidelines in managing prostatic cancer. Furthermore, resources for management of prostatic diseases should be increased and more studies should be conducted.